Aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder triggered by herpes zoster: a case report and literature review - Yingjie Hua; Andi Xu; Huifen Huang; Shuiwei Xia; Junlin Chen; Siyu Lu; Xufang Huang; Zhongwei Zhao; Dan Wu (Journal of International Medical Research)
This paper presents the case of a 45-year-old woman who developed aquaporin-4 (AQP4) antibody-positive neuromyelitis optica spectrum disorder (NMOSD) approximately 6 weeks after a herpes zoster infection. Her initial symptoms included area postrema syndrome, which was marked by persistent nausea, vomiting, and belching. This report also provides a summary of the demographic and clinical features, disease progression, magnetic resonance imaging findings, cerebrospinal fluid analysis, treatment plans, and recovery outcomes of 11 patients—including this case and 10 others reported in the literature since 2008—who developed AQP4 antibody-positive NMOSD following herpes zoster infection. This review aims to improve clinicians’ understanding of the characteristics, treatment, and prognosis of this disease. It also highlights the importance for pain management specialists to consider central pain and use the MIDNIGHTS or VINDψCATE mnemonic devices to systematically consider the differential diagnoses of a patient’s new pain symptoms.